2022
DOI: 10.1002/admi.202200193
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide/Double‐Wall Carbon Nanotube Mixed‐Dimensional Heterostructures

Abstract: Mixed‐dimensional heterostructures which combine materials with different dimensions have emerged to expand the scope and functionality of van der Waals heterostructures. Here, a direct synthesis method of molybdenum disulfide/double‐wall carbon nanotube (MoS2/DWCNT) mixed‐dimensional heterostructures by sulfurating a molten salt, Na2MoO4, on a substrate covered with a DWCNT film is reported. The synthesized heterostructures are comprehensively characterized and their stacking order is confirmed to be MoS2 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[28,29] In particular, to simplify the thermocycling module, our recent work utilizing graphene oxide-associated droplets demonstrated the feasibility for near-infrared (NIR) responsive dPCR. [30] Furthermore, molybdenum disulfide (MoS 2 ) as the new rising 2D nanomaterial, is being investigated for photothermal therapy, [31] optical sensors, [32] field-effect transistors, [33] and so on, owing to its advantages such as attractive physicochemical features, [34] easy surface modification, [35] and high NIR-to-heat conversion property. [36] The advancement of nanotechnology has brought diverse fascinating strategies in developing nucleic acid therapeutics and other personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] In particular, to simplify the thermocycling module, our recent work utilizing graphene oxide-associated droplets demonstrated the feasibility for near-infrared (NIR) responsive dPCR. [30] Furthermore, molybdenum disulfide (MoS 2 ) as the new rising 2D nanomaterial, is being investigated for photothermal therapy, [31] optical sensors, [32] field-effect transistors, [33] and so on, owing to its advantages such as attractive physicochemical features, [34] easy surface modification, [35] and high NIR-to-heat conversion property. [36] The advancement of nanotechnology has brought diverse fascinating strategies in developing nucleic acid therapeutics and other personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the photovoltaic effect is beneficial for fast photoresponse [13] and low power operation while the photogating effect is useful for high optical gain [14]. Very recently, it has been reported that this vdW heterojunction is a very suitable platform to study new 1 Hoon Hahn Yoon, Henry A. Fernandez, Fedor Nigmatulin, Faisal Ahmed, Xiaoqi Cui, Xueyin Bai, Diao Li, Mingde Du, Harri Lipsanen, Zhipei Sun are with the Department of Electronics and Nanoengineering, Aalto University, Fi-00076 Aalto, Finland (corresponding author: Hoon Hahn Yoon, email: hoonhahn.yoon@aalto.fi) photodetection mechanisms such as switchable [15], [16], hybrid [17], [18], negative [19], [20], and anti-ambipolar [21], [22] photoresponses. Based on vdW heterojunctions, a single dominant photodetection mechanism can be switched from one to another [15], [16] for multimode optoelectronics and its logic or neuromorphic computing applications, which is readily achievable by the engineering of band alignment or bending.…”
Section: Introductionmentioning
confidence: 99%